Hot water treatment in apple for pesticide residues degradation - Singh, Ajit Kumar; Sethi, Shruti; Banarjee, Tirthankar; Joshi, Alka; Tippannanavar, Madhu (Indian Horticulture, 2023)
Among the temperate fruit crops, apple is one of the major fruits with a high nutritional profile, which includes vitamins, minerals, antioxidants, and phytochemicals. It is the staple fresh fruit in temperate parts of India as well in the world. Consumption of apples is beneficial for protection against various chronic diseases. Although it is a popular table fruit, its several varieties can also be canned or it can be used for juice, wine, vinegar, and cider making. The changing climate and thereby increased pest-disease incidence has surged the indiscriminate use of pesticides in apple orchards leading to bioaccumulation of residue which is a major concern for consumers. Hence, hot water treatment could be one of the alternative approaches which is safe and ecofriendly.